QUALITY OF PUBLIC TRANSPORTATION SERVICES THROUGH THE “GOLEK BIS (GoBis) SUROBOYO” APPLICATION - Erwing Wahyu Millensyah (Journal Publicuho, 2025)
This study aims to evaluate the quality of the service quality of the Suroboyo GoBis (Golek Bis) application using the five dimensions of SERVQUAL, namely Tangibles, Reliability, Responsiveness, Assurance, and Empathy. The research approach used is qualitative with in-depth interviews, observations, and documentation methods of active users of the application. The results show that the Tangibles dimension is the main strength, characterised by a simple, informative, and easy-to-use application interface, as well as a maintained physical condition of the bus. Dimensity Reliability received a positive rating despite the delay in updating the bus position. On the other hand, the Responsiveness dimension is the most significant weakness due to the slow response to user complaints. The Assurance dimension shows a fairly good sense of security, but is not even in the presence of officers, while the Empathy dimension still has minimal attention to vulnerable groups and user involvement. The research recommends increased responsiveness, optimisation of real-time data updates, equitable distribution of officers at bus stops, addition of inclusive features, and maintenance of the physical quality of services. These findings underscore the importance of overarching improvements to support responsive, inclusive, and sustainable quality of digital public services.